‘PACKHAM’S TRIUMPH’ PEAR RESPONSE TO 1- METHYLCYCLOPROPENE AND NITRIC OXIDE TREATMENTS - Hendges, Marcos Vinícius (2016)
This study aimed at assessing the effect of 1-methylcyclopropene (1-MCP), gas-nitric oxide (NO) and sodium nitroprusside (SNP) on ripening of ‘Packham’s Triumph’ pears. The treatments consisted of T1) control; T2) 300 ppb 1-MCP; T3) 1 mM SNP; T4) 10 ppm NO; and T5) 20 ppm NO. The fruit treated with 1-MCP showed significantly higher values for flesh firmness, texture, and peel green color, besides lower respiratory rates and ethylene production. On the other hand, NO and SNP treatments did not reduce fruit respiratory rate and ethylene production. Flesh firmness and textural features were maintained by treating fruit with 20 ppm NO after leaving chambers. Treatments using 1 mM SNP and 20 ppm NO kept peel green color (higher hue angle) when compared to control, without decreasing fruit yellowing during the shelf life. The application of 300 ppb 1-MCP prevented buttery texture and yellowing in 'Packham’s Triumph' pear fruit during environment condition exposure. The use NO at 20 ppm kept flesh firmness during storage, however, with subsequent reduction of this variable in environmental conditions. The treatments with 1mM SNP and 20 ppm NO maintained green peel of pear fruit, even after exposure to environmental conditions, but not limiting yellowing.